DEMILITARIZED ZONE AND PORT KNOCKING METHODS FOR COMPUTER NETWORK SECURITY - Andik Saputro; Nanang Saputro; Hendro Wijayanto (Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2020)
Currently, the way of network communication has changed a lot. All aspects become very dependent on online services. Employees can work from home, and students of all ages take online classes. The more the public depends on staying connected to the network, the greater potential network attacks to occur. In a computer network, if it is not protected, it will data or file loss, damage to the server system, not being optimal in serving users or even losing valuable institutional assets. The attacks most often used in networks are Port Scanning and DDoS (Distributed Denial Of Service). In this study, the DeMilitarized Zone and Port Knocking methods are combined to secure computer networks. DeMilitarized Zone technique implementation is used to access local servers, so that they can be accessed from outside with Port Knocking technique. To open the access port that is filtered in the router configuration on the server network security system. DeMilitarized Zone and Port Knocking can be implemented on local and long distance networks where if an attacker wants to exploit or attack the main server, the first to be attacked is the firewall server (router). Port Knocking can also be implemented on local and long distance networks with a combined ping request time limit which makes it safer, so that if an attacker wants to access the router, and doesn't know the rules from the remote, what happens is a rejection of port access.